Context-dependent effects of formic acid on olfactory learning and generalisation in ants - Natacha Rossi; Martin Giurfa; Patrizia d’Ettorre (Scientific Reports)
Abstract Animals use learning and memory to recognise cues that predict rewards or punishments, allowing flexible decision-making. When facing new stimuli, they often generalise – responding similarly to different but related cues – enabling adaptive behaviour despite natural variation. Pheromones, chemical signals central to social interactions, are known to affect learning and memory, but their role in generalisation is unknown. This study explores how formic acid, an alarm pheromone in Camponotus aethiops ants, influences odour discrimination and generalisation in an appetitive olfactory discrimination learning task. Using controlled conditioning, we found that formic acid affected learning asymmetrically: it enhanced discrimination when octanal was rewarded and hexanal punished but not when hexanal was rewarded and octanal punished, suggesting a shift in learning priorities. Unexpectedly, formic acid also increased responses to conditioned stimuli and novel odours but only when octanal was the rewarded stimulus. These findings suggest that formic acid modulates associative learning and generalisation in a context-dependent way. Rather than acting solely as an arousal trigger, formic acid appears to reshape cognitive processing by altering stimulus discrimination and odour sensitivity. This highlights a novel role for alarm pheromones in modulating cognition, with broader implications for understanding chemical communication in social insects and beyond.